Glutathione S-Transferase P-Mediated Protein S-Glutathionylation of Resident Endoplasmic Reticulum Proteins Influences Sensitivity to Drug-Induced Unfolded Protein Response - Ye, Zhi-Wei; Zhang, Jie; Ancrum, Tiffany; Manevich, Yefim; Townsend, Danyelle M; Tew, Kenneth D (Antioxidants & redox signaling, 2017)
S-glutathionylation of cysteine residues, catalyzed by glutathione S-transferase Pi (GSTP), alters structure/function characteristics of certain targeted proteins. Our goal is to characterize how S-glutathionylation of proteins within the endoplasmic reticulum (ER) impact cell sensitivity to ER-stress inducing drugs. We identify GSTP to be an ER-resident protein where it demonstrates both chaperone and catalytic functions. Redox based proteomic analyses identified a cluster of proteins cooperatively involved in the regulation of ER stress (immunoglobulin heavy chain-binding protein [BiP], protein disulfide isomerase [PDI], calnexin, calreticulin, endoplasmin, sarco/endoplasmic reticulum Ca -ATPase [SERCA]) that individually co-immunoprecipitated with GSTP (implying protein complex formation) and were subject to reactive oxygen species (ROS) induced S-glutathionylation. S-glutathionylation of each of these six proteins was attenuated in cells (liver, embryo fibroblasts or bone marrow dendritic) from mice lacking GSTP (Gstp1/p2 ) compared to wild type (Gstp1/p2 ). Moreover, Gstp1/p2 cells were significantly more sensitive to the cytotoxic effects of the ER-stress inducing drugs, thapsigargin (7-fold) and tunicamycin (2-fold). Within the family of GST isozymes, GSTP has been ascribed the broadest range of catalytic and chaperone functions. Now, for the first time, we identify it as an ER resident protein that catalyzes S-glutathionylation of critical ER proteins within this organelle. Of note, this can provide a nexus for linkage of redox based signaling and pathways that regulate the unfolded protein response (UPR). This has novel importance in determining how some drugs kill cancer cells. Contextually, these results provide mechanistic evidence that GSTP can exert redox regulation in the oxidative ER environment and indicate that, within the ER, GSTP influences the cellular consequences of the UPR through S-glutathionylation of a series of key interrelated proteins. Antioxid. Redox Signal. 26, 247-261.